Women Empowerment Model Through Corporate Social Responsibility (CSR) Program - Adhianty Nurjanah, Adhianty Nurjanah (2015)
Empowerment of women which aims to enhance the role of women in development in Indonesia has been done. The government's commitment in 2000 was marked by issuing Presidential Decree Number 9 of 2000 on Gender Mainstreaming (PUG) in all areas of development for the implementation of the planning, preparation, implementation and evaluation of government policies that are gender responsive. Indonesian government's efforts to empower women through policy with gender perspective has actually been done. But in reality it turns out that there are imbalances and gender inequality in a variety of access and opportunity contributing to the development and take advantage of the development is still often the case, with women as the recipients of misfortunes (Hubeis, 2010).